1982
DOI: 10.1161/01.hyp.4.3.444
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of pressor responses to norepinephrine and pitressin and potentiation of pressor response to angiotensin II by captopril in human subjects.

Abstract: angiotensin-converting enzyme inhibitor, has been shown to be effective in lowering the blood pressure of hypertensive patients.1 -2 It is generally assumed that the hypotensive effect of captopril may be due to either suppression of angiotensin II (All) formation or potentiation of bradykinin (BK), or a combination of both, 24 since angiotensin converting enzyme is identical to kininase II.5 However, the precise role of the renin-angiotensin and the kallikrein-kinin systems in mediating the hypotensive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…Major changes in vagal tone apparently do not occur with ACEIs (Mancia et al, 1982;Millar et al, 1982;Warren et al, 1983) but regarding the sympathetic system, there are contradictory data in the literature. Thus a sympatho-inhibitory effect of ACEIs has been demonstrated in a number of experimental (Casellas et al, 1980;Antonaccio & Kerwin, 1981;Richer et al, 1983) and clinical (Imai et al, 1982;De Leeuw et al, 1983;Warren et al, 1983) studies but was not found by others (Mancia et al, 1982;Millar et al, 1982;Ibsen et al, 1983).…”
Section: Discussionmentioning
confidence: 89%
“…Major changes in vagal tone apparently do not occur with ACEIs (Mancia et al, 1982;Millar et al, 1982;Warren et al, 1983) but regarding the sympathetic system, there are contradictory data in the literature. Thus a sympatho-inhibitory effect of ACEIs has been demonstrated in a number of experimental (Casellas et al, 1980;Antonaccio & Kerwin, 1981;Richer et al, 1983) and clinical (Imai et al, 1982;De Leeuw et al, 1983;Warren et al, 1983) studies but was not found by others (Mancia et al, 1982;Millar et al, 1982;Ibsen et al, 1983).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the differences in baroreceptor reflex sensitivity observed between these two groups cannot be attributed to changes in basal mean arterial pressure. The findings of Imai and coworkers 33 that the enhanced baroreceptor reflex control of heart rate seen in captopril-treated humans was not accompanied by any changes in mean arterial pressure also suggest that blood pressure is not responsible for the enhanced baroreceptor reflex function. Furthermore, it has recently been reported that the effects of captopril on baroreceptor reflex control of lumbar sympathetic nerve activity are also independent of a change in mean arterial pressure.…”
Section: Discussionmentioning
confidence: 93%
“…Berecek et al 13 showed that chronic central administration of captopril increased baroreceptor reflex control of heart rate in response to an increase in blood pressure in SHR. Imai et al 33 reported that the bradycardia caused by intravenous infusion of norepinephrine or arginine vasopressin was potentiated in normotensive humans given captopril orally. In addition, baroreceptor reflex sensitivity to an increase in blood pressure was enhanced in normotensive men given a single oral dose of enalapril.…”
Section: Discussionmentioning
confidence: 99%
“…A supine measurement was made since captopril increases plasma renin threefold in supine subjects. 27 A captopril-stimulated peripheral renin activity greater than 4 ng/ml/hr was considered elevated. In a recent report, 6 the peripheral renin both before and after administration of captopril, as well as the degree of change in peripheral renin activity, were used to define criteria for "hyperresponsiveness of renin secretion in renovascular hypertensive patients".…”
Section: Methodsmentioning
confidence: 99%